Scalable and efficient key management for mobile WiMAX networks - Sadeghi, Mohammad Mehdi Gilanian (2013)
Efficiency and security are two critical but often conflicting issues in Multicast and Broadcast Service of IEEE 802.16e technology. Hence, it is vital to ensure an optimal scenario where neither security concerns, nor operational efficiency of the network is compromised. This paper proposes a new key management scheme called Scalable and Efficient Key Management Protocol, which uses a binary tree structure together with a B-tree of order 2 structure. It focuses on improving key management performance of the existing techniques in terms of efficiency and scalability, without a loss in security. Scalable and Efficient Key Management Protocol dynamically establishes subgroups based on the current number of Mobile Stations in a WiMAX Base Station's coverage area. This will optimize the communications, computational and storage costs of the network. In addition, the scheme guarantees strong network scalability. Both analytical and simulation approaches have been carried out, and the results showed that the proposed scheme exhibits superior performance in terms of efficiency and scalability compared with existing schemes.